Monitoring of physical activity promotion in children and adolescents in the EU: current status and future perspectives. (17th November 2021) - Marzi, Isabel; Tcymbal, Antonina; Gelius, Peter; Abu-Omar, Karim; Reimers, Anne K; Whiting, Stephen; Wickramasinghe, Kremlin
Abstract: Background: Policy action is required to address physical inactivity in boys and girls. This action can be supported by international data collection, comparisons and sharing of good practices. Thus, this study aims to present and discuss the ongoing monitoring of physical activity (PA) indicators in children and adolescents in the 28 EU Member States. Methods: Data on PA recommendations, PA prevalence, physical education (PE) and PA promotion programs for children and adolescents were provided by governments in a joint EU/WHO survey on the implementation status of the EU Council Recommendation on Health-Enhancing Physical Activity (HEPA) across Sectors. Results: In 23 countries, national recommendations on PA are available. Detailed PA prevalence data among children and adolescents was available in 27 countries, in most cases separately for sex/gender and age groups. The total amount of PE lessons in schools differed greatly between countries and lessons were predominantly mandatory. After-school HEPA promotion programs were mostly implemented in EU Member States (78.6%), followed by active school breaks (57.1%), active travel to school (57.1%) and active breaks during school lessons (53.6%). Conclusions: This study summarizes the monitoring of PA indicators among children and adolescents in all EU Member States by providing a comprehensive overview of the status of PA promotion and monitoring across the region. Based on our findings, it could be concluded that the current EU monitoring system on PA promotion should be adapted to provide evidence that can inform future policy development.